Perovskite type ceramic material and preparation method and application thereof

By preparing perovskite-type ceramic materials with the general formula of (Bay1Sry2Cay3) FexO3, the problem of poor application performance of perovskite-type wave absorbing materials in extreme environments is solved, and efficient electromagnetic wave absorption performance is achieved.

CN119797903AActive Publication Date: 2025-04-11ZHENGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510014006.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Existing perovskite-type absorbing materials have poor application performance in extreme environments.

Method used

The chemical formula of a perovskite ceramic material is provided as (Bay1Sry2Cay3)FexO3, wherein x=0.5~1.5, y1=y2=y3=0.2>0.4. The material is prepared by mixing a strontium source, a barium source, a calcium source, an iron source with a precipitant and calcining.

Benefits of technology

When this material is combined with paraffin, the thickness is 1.2mm, the absorption bandwidth can reach 4.16GHz, and the minimum reflection loss can reach -40.58dB. It has the characteristics of effective absorption bandwidth and high absorption strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797903A_ABST
    Figure CN119797903A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-entropy ceramic materials, and discloses a perovskite type ceramic material as well as a preparation method and application thereof. The general chemical formula of the perovskite type ceramic material disclosed by the invention is (Bay1Sry2Cay3) FexO3, in which x is equal to 0.5 to 1.5, y1 is equal to y2, y3 is equal to 0.2 to 0.4. The composite mass ratio of the obtained perovskite type ceramic material to the paraffin is 9: 1, and when the thickness is 1.2 mm, the absorption frequency band width can reach 4.16 GHz, the lowest reflection loss can reach-40.58 dB, and the perovskite type ceramic material has the characteristics of wide effective absorption frequency band and high absorption strength under the condition of low thickness. Moreover, the preparation method of the material takes water as a solvent, does not need to use highly toxic chemical reagents, is environment-friendly and pollution-free, and is simple in preparation process, low in cost and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy ceramic materials, and in particular to a perovskite ceramic material and a preparation method and application thereof. Background Art

[0002] Since the 21st century, science and technology have developed rapidly, especially electronic information technology, which has brought great convenience to human life and work. However, a large number of electronic products have brought great harm while bringing convenience. Excessive use of electronic products will lead to serious electromagnetic radiation and interference. In addition, the widespread application of electromagnetic waves in science and technology has also brought a series of social problems, which not only affects communication, but also directly or indirectly harms human health. Therefore, electromagnetic radiation has become another major source of pollution in the 21st century after air pollution, water pollution, and light pollution. At the same time, with the in-depth development of precision-guided weapons, stealth weapons have become a key research project for the armaments of various countries.

[0003] Absorbing materials are one of the key materials in defense and civilian fields such as military stealth, microwave communications, and electromagnetic radiation protection. Absorbents with good absorbing properties are the core of absorbing materials. In order to meet the requirements of thinness, lightness, width, and strength, the research on absorbents is also developing towards high efficiency, compositeness, compatibility, and intelligence.

[0004] Perovskite material is a kind of microwave absorbing material with strong dielectric loss and good stability. It is a kind of dielectric loss type microwave absorbing material that has attracted much attention. Yu Man et al. prepared Fe by sol-gel method. 3+ Doped lanthanum nickelate perovskite ceramics, Fe 3+ The best absorption performance is achieved when the doping amount is 0.05, the matching thickness is 1.40 mm, the maximum peak value can reach -18.145 dB, and the bandwidth below -10 dB is 1.42 GHz (9.38-10.8 GHz) (Journal of Aeronautical Materials. 2023, 43(06)). The Che Renchao team of Fudan University synthesized a uniform BaTiO with concave holes and central holes by hydrothermal method. 3 Nanorings, BaTiO was tested in the 2-18 GHz microwave frequency band 3 Nano-torus and BaTiO 3 Microwave absorption properties of solid nanoparticles, BaTiO 3 The maximum reflection loss of the nano-annular surface at 11.36 GHz is -28.38 dB, and the maximum reflection loss at 16.32 GHz is -12.87 dB. In the range of 8 to 12 GHz, the reflection loss increases by nearly 120% (Nanoscale, 2011, 3(9): 3860-3867). Cheng et al. 1-x Sr x MnO3 By compounding with carbonyl iron, the polarization and magnetization of the material are enhanced by utilizing the interface effect, so that the reflection loss of the material in the range of 2 to 18 GHz is less than -10 dB (Nature, 2020, 578(7794): 251-260).

[0005] At present, the research on perovskite-type absorbing materials mainly focuses on the doping of materials to construct composite absorbing materials, but there is still a large gap compared to the requirements for use in extreme environments. Summary of the invention

[0006] The purpose of the present invention is to provide a perovskite ceramic material and a preparation method and application thereof, so as to solve the problem that the existing perovskite absorbing materials have poor application performance in extreme environments.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a perovskite ceramic material, the chemical formula of the perovskite ceramic material is: (Ba y1 Sr y2 Ca y3 )Fe x O 3 , where x = 0.5 to 1.5, y 1 =y 2 =y 3 =0.2~0.4.

[0009] The present invention also provides a method for preparing a perovskite ceramic material, comprising the following steps:

[0010] A strontium source, a barium source, a calcium source, an iron source and a precipitant are mixed and calcined to obtain a perovskite-type ceramic material.

[0011] Preferably, in the preparation method, the strontium source includes strontium chloride and / or strontium nitrate; the barium source includes barium chloride and / or barium nitrate; the calcium source includes calcium chloride and / or calcium nitrate; and the iron source includes ferric nitrate and / or ferric chloride.

[0012] Preferably, in the preparation method, the precipitant comprises a mixture of sodium carbonate and an inorganic base;

[0013] The inorganic base includes sodium hydroxide and / or ammonia water.

[0014] Preferably, in the preparation method, the mass ratio of the sodium carbonate to the inorganic base is 1-2:1-2.

[0015] Preferably, in the preparation method, the mass ratio of the total mass of the strontium source, the barium source, the calcium source, and the iron source to the mass of the precipitant is 17-19:6-8.

[0016] Preferably, in the preparation method, the calcination temperature is 900-1300° C., the heating rate to the desired calcination temperature is 4-6° C. / min, and the holding time after reaching the desired calcination temperature is 3-5 h.

[0017] Preferably, in the preparation method, the manner of mixing the strontium source, barium source, calcium source, iron source and precipitant is specifically as follows:

[0018] Mixing a strontium source, a barium source, a calcium source, an iron source and water to obtain an inorganic salt solution; mixing a precipitant with water to obtain a precipitant solution; mixing the inorganic salt solution with the precipitant solution, and sequentially performing standing, filtering, washing and drying;

[0019] In the inorganic salt solution, the ratio of the total mass of the strontium source, the barium source, the calcium source, and the iron source to the volume of the water is 17-19 g: 90-110 mL;

[0020] In the precipitant solution, the ratio of the mass of the precipitant to the volume of the water is 6-8 g: 90-110 mL;

[0021] The stirring rate of the inorganic salt solution and the precipitant solution is 500-800 r / min.

[0022] Preferably, in the preparation method, the inorganic salt solution and the precipitant solution are mixed by dropwise addition;

[0023] The dropping rate is 10-20 mL / min.

[0024] The present invention also provides an application of a perovskite ceramic material in electromagnetic wave absorption.

[0025] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The perovskite ceramic material provided by the present invention is (Ba y1 Sr y2 Ca y3 )Fe x O 3 , where x = 0.5 to 1.5, y 1 =y 2 =y 3 =0.2~0.4, its composite mass ratio with paraffin is 9:1, when the thickness is 1.2mm, the absorption bandwidth can reach 4.16GHz, and the minimum reflection loss can reach -40.58dB. It has the characteristics of wide effective absorption bandwidth and high absorption intensity at low thickness.

[0027] (2) The present invention also provides a method for preparing the perovskite-type ceramic material, which uses water as a solvent, does not require the use of highly toxic chemical reagents, and is environmentally friendly and pollution-free; and the preparation process is simple and low-cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments or the prior art are briefly introduced below.

[0029] Figure 1 is a SEM image of the perovskite ceramic material of Example 1;

[0030] Figure 2 is a SEM image of the perovskite ceramic material of Example 2;

[0031] Figure 3 The reflection loss result of the perovskite ceramic material of Example 2 at a thickness of 1 to 5 mm;

[0032] Figure 4 is a SEM image of the perovskite ceramic material of Example 3;

[0033] Figure 5 XRD diagrams of the perovskite ceramic materials of Examples 1 to 3;

[0034] Figure 6 The reflection loss results of the perovskite ceramic materials of Examples 1 to 3;

[0035] Figure 7 These are the impedance matching results of the perovskite ceramic materials of Examples 1 to 3. DETAILED DESCRIPTION

[0036] The present invention provides a perovskite ceramic material, the chemical formula of the perovskite ceramic material is: (Ba y1 Sr y2 Ca y3 )Fe x O 3 , where x = 0.5 to 1.5, y 1 =y 2 =y 3 =0.2~0.4.

[0037] In the present invention, x in the general chemical formula is preferably 0.7 to 1.4, more preferably 0.8 to 1.1, and even more preferably 1.

[0038] In the present invention, y in the chemical formula 1 =y 2 =y 3It is preferably 0.22 to 0.36, more preferably 0.29 to 0.34, and still more preferably 0.33.

[0039] In the present invention, the particle size of the perovskite ceramic material is preferably 5 to 30 μm, more preferably 10 to 25 μm, and even more preferably 10 to 20 μm.

[0040] The present invention also provides a method for preparing a perovskite ceramic material, comprising the following steps:

[0041] A strontium source, a barium source, a calcium source, an iron source and a precipitant are mixed and calcined to obtain a perovskite-type ceramic material.

[0042] In the present invention, the method of mixing the strontium source, barium source, calcium source, iron source and precipitant is preferably:

[0043] The strontium source, barium source, calcium source, iron source and water are mixed to obtain an inorganic salt solution; the precipitant is mixed with water to obtain a precipitant solution; the inorganic salt solution and the precipitant solution are mixed, and the mixture is allowed to stand, filtered, washed and dried in sequence.

[0044] In the present invention, in the inorganic salt solution, the ratio of the total mass of the strontium source, barium source, calcium source and iron source to the volume of the water is preferably 17-19 g:90-110 mL, more preferably 17.8-18.6 g:95-105 mL, and more preferably 18.3-18.4 g:100 mL.

[0045] In the present invention, in the precipitant solution, the ratio of the mass of the precipitant to the volume of the water is preferably 6-8 g:90-110 mL, more preferably 6.5-7.2 g:95-105 mL, and more preferably 6.7-6.8 g:100 mL.

[0046] In the present invention, the stirring rate of the inorganic salt solution and the precipitant solution is preferably 500 to 800 r / min, more preferably 650 to 800 r / min, and more preferably 700 to 750 r / min.

[0047] In the present invention, the inorganic salt solution and the precipitant solution are preferably mixed by dropwise addition.

[0048] In the present invention, the dripping is preferably adding the inorganic salt solution dropwise into the precipitant solution.

[0049] In the present invention, the dropping rate is preferably 10 to 20 mL / min, more preferably 12 to 18 mL / min, and more preferably 15 to 16 mL / min.

[0050] In the present invention, the standing time is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and even more preferably 1.8 to 2.2 hours.

[0051] In the present invention, the filtering method is preferably suction filtration.

[0052] In the present invention, the filtration equipment is preferably a suction filter.

[0053] In the present invention, the washing reagents are preferably water and ethanol.

[0054] In the present invention, the washing method is preferably to use water and ethanol in sequence.

[0055] In the present invention, the target pH of the washing is preferably 6.5 to 7.5, more preferably 6.7 to 7.3, and even more preferably 6.9 to 7.1.

[0056] In the present invention, the drying temperature is preferably 100-110°C, more preferably 100-106°C, and more preferably 100-102°C; the drying time is preferably 7-9h, more preferably 7.5-8.5h, and more preferably 7.8-8.2h.

[0057] In the present invention, the cooling method is preferably natural cooling.

[0058] In the present invention, the target temperature of the cooling is preferably 20 to 30°C, more preferably 22 to 28°C, and even more preferably 24 to 26°C.

[0059] In the present invention, the strontium source preferably includes strontium chloride and / or strontium nitrate, and more preferably strontium chloride (strontium chloride hexahydrate).

[0060] In the present invention, the barium source preferably includes barium chloride and / or barium nitrate, and more preferably barium chloride (barium chloride dihydrate).

[0061] In the present invention, the calcium source preferably includes calcium chloride and / or calcium nitrate, and more preferably calcium chloride.

[0062] In the present invention, the iron source preferably includes ferric nitrate and / or ferric chloride, and more preferably ferric nitrate (ferric nitrate nonahydrate).

[0063] In the present invention, the precipitant preferably comprises a mixture of sodium carbonate and an inorganic base. Using sodium carbonate and an inorganic base as precipitants can better precipitate metal ions.

[0064] In the present invention, the inorganic base preferably includes sodium hydroxide and / or ammonia water, and more preferably sodium hydroxide.

[0065] In the present invention, the mass ratio of the sodium carbonate to the inorganic base is preferably 1-2:1-2, more preferably 1-1.5:1-1.5, and more preferably 1:1.13-1.14.

[0066] In the present invention, the mass ratio of the total mass of the strontium source, barium source, calcium source and iron source to the precipitant is preferably 17-19:6-8, more preferably 17.8-18.6:6.5-7.2, and more preferably 18.3-18.4:6.7-6.8.

[0067] In the present invention, the calcination temperature is preferably 900-1300°C, more preferably 1000-1200°C, and more preferably 1100-1120°C; the heating rate to the desired calcination temperature is preferably 4-6°C / min, more preferably 4.5-5.5°C / min, and more preferably 5-5.2°C / min; the holding time after reaching the desired calcination temperature is preferably 3-5h, more preferably 3.5-4.5h, and more preferably 4-4.1h.

[0068] In the present invention, the calcination preferably further includes cooling.

[0069] In the present invention, the cooling method is preferably natural cooling.

[0070] In the present invention, the target temperature of the cooling is preferably 20 to 30°C, more preferably 22 to 28°C, and even more preferably 24 to 26°C.

[0071] The present invention also provides an application of a perovskite ceramic material in electromagnetic wave absorption.

[0072] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.

[0073] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Example 1

[0075] This embodiment provides a perovskite ceramic material (Ca 0.33 Sr 0.33 Ba 0.33 )FeO 3 The preparation method comprises the following steps:

[0076] Weigh 2.6662 g of strontium chloride hexahydrate, 12.1197 g of ferric nitrate nonahydrate, 1.1098 g of calcium chloride and 2.4426 g of barium chloride dihydrate and dissolve them in 100 mL of distilled water to obtain an inorganic salt solution;

[0077] Weigh 3.6 g of sodium hydroxide and 3.1797 g of sodium carbonate and dissolve them in 100 mL of distilled water to obtain a precipitant solution;

[0078] The inorganic salt solution was added dropwise to the precipitant solution at a rate of 15 mL / min, and stirred while adding dropwise at a rate of 750 r / min. After the addition was completed, the solution was allowed to stand for 2 h, and then filtered with a suction filter, and washed with distilled water and anhydrous ethanol in sequence until the precipitate had a pH of 7.0, and dried in a forced air drying oven at 100°C for 8 h, and naturally cooled to 24°C to obtain an intermediate product.

[0079] The intermediate product was placed in a muffle furnace, heated to 1000° C. at a rate of 5° C. / min in an air atmosphere, calcined for 4 hours, and then naturally cooled to 25° C. to obtain a perovskite ceramic material.

[0080] The perovskite ceramic material prepared in Example 1 was subjected to SEM analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the sample morphology is lamellar, approximately hexagonal, and the particle width is 15 to 20 μm.

[0081] Example 2

[0082] This embodiment provides a perovskite ceramic material (Ca 0.33 Sr 0.33 Ba 0.33 )FeO 3 The preparation method is different from that of Example 1 in that the calcination temperature is modified to 1100° C., and other parameter conditions are the same as those of Example 1.

[0083] The perovskite ceramic material prepared in Example 2 was subjected to SEM analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the sample morphology is a hexagonal layered structure and the particle size is about 5 μm.

[0084] The perovskite ceramic material prepared in Example 2 was tested for reflection loss at a thickness of 1 to 5 mm. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the ceramic product prepared in Example 2 has effective electromagnetic wave absorption performance within the thickness range of 1 to 5 mm, and its effective wave absorption bandwidth can effectively cover 2 to 18 GHz.

[0085] Example 3

[0086] This embodiment provides a perovskite ceramic material (Ca 0.33 Sr 0.33 Ba 0.33 )FeO 3 The preparation method is different from that of Example 1 in that the calcination temperature is modified to 1200° C., and other parameter conditions are the same as those of Example 1.

[0087] The perovskite ceramic material prepared in Example 3 was subjected to SEM analysis, and the results are as follows: Figure 4 As shown. Figure 4 It can be seen that the sample particles gradually become larger, with a particle size of 20 to 30 μm.

[0088] The perovskite ceramic materials prepared in Examples 1 to 3 were subjected to X-ray diffraction analysis. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that at a calcination temperature of 1000°C, the perovskite ceramic material has a second phase with a non-perovskite structure. As the calcination temperature reaches 1100°C, the second phase peak disappears and a single phase is formed. At a temperature of 1200°C, the second phase diffraction peak appears again.

[0089] The perovskite ceramic materials prepared in Examples 1 to 3 were compounded with paraffin wax at a mass ratio of 9:1, and reflection loss analysis was performed at a thickness of 1.2 mm. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that when the calcination temperature is 1100℃, the perovskite ceramic material shows excellent electromagnetic wave absorption performance, with the minimum reflectivity reaching -40.58dB and the effective absorption bandwidth reaching 4.16GHz. Calcination temperatures that are too low (1000℃) or too high (1200℃) are not conducive to improving the electromagnetic wave absorption performance of the material.

[0090] The perovskite ceramic materials prepared in Examples 1 to 3 were compounded with paraffin wax at a mass ratio of 9:1, and an impedance matching test was performed at a thickness of 1.2 mm. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that excellent wave impedance matching characteristics are exhibited when the calcination temperature is 1100° C. and 1200° C., while the wave impedance matching characteristics are poor at 1000° C.

[0091] It can be seen from the above embodiments that the perovskite ceramic material provided by the present invention has both dielectric loss and magnetic loss properties. When compounded with paraffin in a mass ratio of 9:1 and having a thickness of 1.2 mm, the effective absorption bandwidth can reach 4.16 GHz and the minimum reflection loss can reach -40.58 dB; it has the characteristics of a wide effective absorption bandwidth and high absorption intensity at a low thickness.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A perovskite ceramic material, characterized in that: The general chemical formula of the perovskite ceramic material is: y1 Sr y2 Ca y3 )Fe x O3, wherein x=0.5~1.5, y1=y2=y3=0.2~0.

4.

2. The method for preparing a perovskite ceramic material according to claim 1, characterized in that: It includes the following steps: A strontium source, a barium source, a calcium source, an iron source and a precipitant are mixed and calcined to obtain a perovskite-type ceramic material.

3. The preparation method according to claim 2, characterized in that: The strontium source includes strontium chloride and / or strontium nitrate; the barium source includes barium chloride and / or barium nitrate; the calcium source includes calcium chloride and / or calcium nitrate; and the iron source includes ferric nitrate and / or ferric chloride.

4. The preparation method according to claim 2, characterized in that: The precipitant comprises a mixture of sodium carbonate and an inorganic base; The inorganic base includes sodium hydroxide and / or ammonia water.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the sodium carbonate to the inorganic base is 1-2:1-2.

6. The preparation method according to any one of claims 2 to 4, characterized in that: The mass ratio of the total mass of the strontium source, the barium source, the calcium source and the iron source to the mass ratio of the precipitant is 17-19:6-8.

7. The preparation method according to claim 2, characterized in that: The calcination temperature is 900-1300° C., the heating rate to the required calcination temperature is 4-6° C. / min, and the insulation time after reaching the required calcination temperature is 3-5 hours.

8. The preparation method according to claim 2, characterized in that: The method of mixing the strontium source, the barium source, the calcium source, the iron source and the precipitant is specifically as follows: Mixing a strontium source, a barium source, a calcium source, an iron source and water to obtain an inorganic salt solution; mixing a precipitant with water to obtain a precipitant solution; mixing the inorganic salt solution with the precipitant solution, and sequentially performing standing, filtering, washing and drying; In the inorganic salt solution, the ratio of the total mass of the strontium source, the barium source, the calcium source, and the iron source to the volume of the water is 17-19 g: 90-110 mL; In the precipitant solution, the ratio of the mass of the precipitant to the volume of the water is 6-8 g: 90-110 mL; The stirring rate of the inorganic salt solution and the precipitant solution is 500-800 r / min.

9. The preparation method according to claim 8, characterized in that: The inorganic salt solution and the precipitant solution are mixed by dropwise addition; The dropping rate is 10-20 mL / min.

10. Use of the perovskite ceramic material according to claim 1 or the perovskite ceramic material prepared by the preparation method according to any one of claims 2 to 9 in electromagnetic wave absorption.

Citation Information

Patent Citations

  • Monolithic catalyst as well as preparation method and application thereof

    CN114832811A

  • Perovskite type ceramic material and preparation method and application thereof

    CN116589264A

  • High-entropy perovskite type fuel electrode material, preparation method and application

    CN118996477A

  • Medium-entropy perovskite oxygen carrier and preparation method and application thereof

    US20240116771A1

  • Electromagnetic wave-absorbing material and electromagnetic wave absorber

    WO2020170608A1